Mercury and antimony in wastewater: fate and treatment - Hargreaves, Andrew J.; Vale, Peter C. J.; Whelan, Jonathan; Constantino, Carlos; Dotro, Gabriela; Cartmell, Elise (Springer, 2016)
It is important to understand the fate of Hg and Sb within the wastewater treatment process so as to examine potential treatment options and to ensure compliance with regulatory standards. The fate of Hg and Sb was investigated for an activated sludge process treatment works in the UK. Relatively high crude values (Hg 0.092 μg/L, Sb 1.73 μg/L) were observed at the works, whilst low removal rates within the primary (Hg 52.2 %, Sb 16.3 %) and secondary treatment stages (Hg 29.5 %, Sb −28.9 %) resulted in final effluent concentrations of 0.031 μg/L for Hg and 2.04 μg/L for Sb. Removal of Hg was positively correlated with suspended solids (SS) and chemical oxygen demand (COD) removal, whilst Sb was negatively correlated. Elevated final effluent Sb concentrations compared with crude values were postulated and were suggested to result from Sb present in returned sludge liquors. Kepner Tregoe (KT) analysis was applied to identify suitable treatment technologies. For Hg, chemical techniques (specifically precipitation) were found to be the most suitable whilst for Sb, adsorption (using granulated ferric hydroxide) was deemed most appropriate. Operational solutions, such as lengthening hydraulic retention time, and treatment technologies deployed on sludge liquors were also reviewed but were not feasible for implementation at the works.
Keywords: Mercury; Antimony; Precipitation; Adsorption; Wasterwater; Kepner Tregoe